(untitled) (Studia Prawnicze / The Legal Studies, 1990)
Gwarancja w kodeksie cywilnym ma już ponad 20 lat i nie była dotąd zmieniana, choć w doktrynie panuje daleko idąca zgodność, że nie zabezpiecza w takim stopniu, jak powinna, interesów kupującego: że chroni bardziej sprzedawcę niż nabywcę. Dyspozytywność unormowania gwarancji i zniweczenie na długi okres (przeważnie jednego roku) uprawnień z tytułu rękojmi uzależniają kupującego „od władzy” gwaranta. Narzucenie przez gwaranta treści postanowień gwarancyjnych i faktyczny przymus przyjęcia gwarancji (pozbawiony poza obrotem uspołecznionym podstaw prawnych) zmniejszają zacznie korzyści, które powinny z niej płynąć dla kupującego. O niedoskonałości gwarancji w kodeksie cywilnym świadczą liczne orzeczenia Sądu Najwyższego, które nie tylko stanowią twórczą wykładnię przepisów k.c., lecz w istocie poprawiają regulację kodeksową. Nie zawsze jednak biegną za tym orzeczenia sądów niższej instancji, chociaż też wiele wyroków chroniących konsumenta zasługuje na uznanie. Zasługą Sądu Najwyższego jest wydanie wielu doniosłych rozstrzygnięć, które pozwoliły na ustalenie linii orzecznictwa chroniącej słabszą stronę w tym stosunku prawnym, tj. kupującego. Warranty in the Civil Code has been now present for more than 20 years and has not yet been amended, although there is a far-reaching consensus in doctrine that it does not protect the interests of the buyer as much as it should: that it protects the seller more than the buyer. The discretionary nature of the warranty provisions and the nullification of warranty rights for a long period (usually one year) make the buyer “dependent on the authority” held by the guarantor. The imposition of the content of the guarantee provisions by the guarantor and the de facto compulsion to accept the warranty (which has no legal basis outside the society-based trade) reduce the benefits that the buyer should enjoy. The inadequacy of warranty in the Civil Code is proven by the numerous decisions of the Supreme Court, which do not only provide the creative interpretation of Civil Code provisions, but actually improve the codified regulations. However, lower instance court rulings do not always follow the above, although there are also many judgements protecting the consumer that deserve recognition. The Supreme Court should be credited with issuing a number of momentous decisions that have established a line of jurisprudence protecting the weaker party in this legal relationship, i.e. the buyer.